Variaciones de la temperatura corporal de los gatos sometidos a procedimientos anestésicos en cirugías de esterilización, pasantía en clínica vet.co science segundo semestre 2022 - Mendoza Criales, Amanda Paola; Hernández Esparza, Janeth Andrea (Universidad Antonio Nariño, 2023)
Perioperative hypothermia is a very common complication in surgical patients (60-80%), although in veterinary medicine these data are not well documented, a very similar number is estimated and even higher due to some other factors. Predisposing factors such as the relationship between surface area and mass (in small animals), decreased heat production capacity in cachectic patients or neonates, and due to the little knowledge and control that the veterinarian has over this variable. In veterinary patients, specifically in dogs and cats, it is defined as any